P07.07 Multiplexing sti causing pathogens using mnazyme qpcr: a novel real-time technology with a superior capacity for multiplexing. (13th September 2015) - Erskine, SM; Tan, L; Walker, S; Denver, C; Mokany, E
Abstract : Introduction: The pressure for faster, cheaper, better sample testing has resulted in an increasing need for multiplexed assays. Current real-time chemistries are expensive and/or difficult to multiplex. MNAzyme qPCR is a novel real-time technology that provides a powerful tool for molecular diagnostics with multiple advantages over other real-time chemistries. A multiplex MNAzyme qPCR panel was used for the identification of causative bacterial pathogens important for prompt and proper treatment of STIs. Methods: An MNAzyme qPCR panel was developed for the multiplexed detection of Mycoplasma genitalium, Mycoplasma hominis, Ureaplasma parvum and Ureaplasma urealyticum together with a DNA extraction control. MNAzymes are comprised of two DNA partzymes, which come together only in the presence of PCR amplicons, to form active enzymes that modify universal reporter probes and produce signals that are monitored in real-time. Since signal production requires the binding of two partzymes and two PCR primers to a target, this approach has higher specificity than other chemistries, making it ideal for molecular diagnostics. The use of a series of well-characterised, universal probes provides many advantages over target specific probes. They result in reliable, consistent performance when coupled to any target and facilitate rapid and simple development of multiplex tests. Results: The STI panel showed robust performance in multiplex with high analytical specificity and sensitivity. The R 2 for all targets was above 0.99 and PCR efficiencies ranged from 90% to 110%. No inter-panel cross-reactivity was observed and no cross-reactivity was detected using a wide range of non-target organisms. Conclusion: MNAzyme qPCR provides a superior approach to real-time PCR with the advantages of greater specificity, robust multiplex performance, reduced cost, and it is more amenable than other technologies for the rapid development of multiplex assays. These features have been demonstrated through the STI MNAzyme qPCR panel. Disclosure of interest statement: SpeeDx is the developer and manufacturer of the assay evaluated in this study.